The Individual Art of Speaking Well – teaching it by means of group and project work - Juel, Henrik (Dansk Universitetspædagogisk Tidsskrift, 2010)
Based on experimental workshops in rhetoric and free public speaking involving student performance at Speaker’s Corner, London, this article argues that a focus on highly individual skills is compatible with group work and socio-cultural learning principles. The author maintains that collective responsibility may inspire the peak performance of the individual.